A study of woodcarving motifs on traditional Malay houses in Kuala Pilah, Negeri Sembilan / Juliana Adlin Ahmad, Arba’iyah Ab. Aziz and Mohamad Kamal Abd. Aziz - Ahmad, Juliana Adlin; Ab. Aziz, Arba’iyah; Abd. Aziz, Mohamad Kamal (Faculty of Art and Design, 2022)
Malay woodcarving contains a rich history derivative of the cultural identity, beliefs, customs, and traditions of the Malay people. It is deemed as an important and integral part of vernacular architecture in Peninsular Malaysia. Traditional Malay houses are representative of the ancient aptitudes of the workmanship with opulent ornamentations as they reflect the socio-cultural identity of the Malay world. Previous research on woodcarving motifs immensely centred on the east coast of Malaysia, requiring more investigations of woodcarvings motifs on the southwest coast. The objective of this study is to identify the woodcarving motifs on traditional Malay houses in Kuala Pilah, Negeri Sembilan by using a qualitative method such as primary data involving photography. The results indicated different categories of motifs such as fauna, flora, geometry, still life and combination motifs. On this basis, it is hoped that this study could serve as a reference concerning the cultural heritage of woodcarving motifs and Malay traditional houses in Kuala Pilah, Negeri Sembilan and it is recommended that further exploration should be carried out more concerning woodcarving motifs and traditional Malay houses on the southwest coast.